1996
DOI: 10.2307/3432707
|View full text |Cite
|
Sign up to set email alerts
|

Teplice Program: The Impact of Air Pollution on Human Health

Abstract: Reproductive studies were conducted in both males and females. A study of the effects of exposure on pregnancy and birth found an excess prevalence of low birth weight and premature births in Teplice; these adverse effects were more common in infants conceived in the winter and whose mothers were smokers. Based on questionnaires and medical examination, the reproductive development of young men was not different between districts and seasons, however, measures of semen quality suggest that exposure to high lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 14 publications
1
19
0
Order By: Relevance
“…Morris et al (2003) found no statistically significant excess risk of low birth weight in populations living near special waste landfill sites in Scotland. In contrast, after controlling for potential confounders, Sram et al (1996) report an increased frequency of low birth weight deliveries in a heavily industrial region of the Czech Republic compared with the control region. Elliott et al (2001) studied 9,565 landfill sites in Great Britain and found a small, elevated risk of low birth-weight deliveries among women living within 2 km of a landfill.…”
Section: Residential Exposure To Industrial Waste and Reproductive Hementioning
confidence: 64%
“…Morris et al (2003) found no statistically significant excess risk of low birth weight in populations living near special waste landfill sites in Scotland. In contrast, after controlling for potential confounders, Sram et al (1996) report an increased frequency of low birth weight deliveries in a heavily industrial region of the Czech Republic compared with the control region. Elliott et al (2001) studied 9,565 landfill sites in Great Britain and found a small, elevated risk of low birth-weight deliveries among women living within 2 km of a landfill.…”
Section: Residential Exposure To Industrial Waste and Reproductive Hementioning
confidence: 64%
“…However, it was only recently when several studies demonstrated statistical associations between high ambient air pollution levels and human health, including morbidity and mortality in the Czech Republic (Bobak and Leon 1992;Jelinkova and Branis 2001;Sram et al 1996). The political and successive economical changes in Central and Eastern Europe at the end of 1980s significantly influenced the principal sources of urban air pollution (Moldan and Schnoor 1992).…”
Section: Introductionmentioning
confidence: 99%
“…The higher the exposure, the more severe are the adverse health effects. No data on environmental inequity have so far been gathered in the Czech Republic; however, epidemiological research has shown that exposure to air pollution has adverse health effects in many Czech regions (Bobak and Leon, 1992;Sram et al, 1996;Katsouyanni et al, 1997;Peters et al, 2000;Jelinkova and Branis, 2001;Branis et al, 2011). New studies combining epidemiological, socio-economic and air pollution variables will be needed to reveal whether or not low SES significantly contributes to health problems in socially deprived groups of people also in the Czech Republic (and in other countries in transition).…”
Section: Discussionmentioning
confidence: 99%